PENDIDIKAN INKLUSIF MULTIKULTURAL: ISLAM SEBAGAI WAWASAN PENDIDIKAN INKLUSIF - Mohamad Solihin; Ahmad Buchori Muslim (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2023)
This research aims to provide alternative ideas in overcoming exclusive religious practices that seem to be influenced by religious learning methods in schools that have not been able to change and form inclusive attitudes in students. The significance of efforts to restructure the elements of Islamic education that have an inclusive-multicultural orientation, especially in designing the curriculum, the characteristics of educators, and the efficiency of learning methods. This research is a type of desk research, based on a theoretical-philosophical study of various literatures on the concept of education that engages and sharpens the analysis and promotes the researcher's theoretical sensitivity when examining the concept of more creative inclusive education and its application through the Islamic education curriculum. The results of this study show that Islam as a practice of inclusive education through curriculum and competent teachers. Inclusive religious education, emphasizing the importance of developing an understanding of diversity, can be an effective model in transforming religious education in Indonesia's diverse society. Inclusive religious education also acts as a religious learning tool that contributes to the formation of learners' moderate attitudes.